Building a Fair Criminal Justice System: The Urgency of a Single Prosecution System for Prosecutors and Police - Purbowo, Alma Aulia Shafa; Purnomo, Rafel Nanda; Frans, Mardian Putra (Faculty of Law, Udayana University, 2025)
The Indonesian criminal justice system faces complex challenges in coordination and effectiveness of law enforcement, particularly between the police and the prosecutor's office. The dualism of investigative authority that has existed for some time has given rise to various structural problems, resulting in legal uncertainty and reducing the quality of criminal law enforcement. This study focuses on analyzing the urgency of implementing a Single Prosecution System as a reformative solution in building a more equitable and effective criminal justice system. The concept of a Single Prosecution System is of particular concern because in the practice of law enforcement in Indonesia, there is still a division of dual authority, where prosecutors and the police both have the authority to investigate certain cases such as corruption and gross human rights violations. This condition often leads to unclear tasks between institutions, weak coordination, and overlapping authorities, which result in inconsistencies in the handling of criminal cases. The purpose of this study is to identify the weaknesses of the current criminal justice system and analyze how the implementation of the Single Prosecution System can be a solution to create an integrated, effective, and fair criminal justice system. This study uses a legal-normative approach with secondary data consisting of primary and secondary legal materials. Data analysis was conducted qualitatively. The results of the study indicate that reforming the criminal justice system through the implementation of a Single Prosecution System can eliminate overlapping authority between prosecutors and the police, strengthen institutional coordination, and create an Indonesian criminal justice system that guarantees legal certainty and justice for the community.